Penggunaan Bahasa Indonesia Sebagai Alat Komunikasi Antar Budaya - Syafina Maulani; Rina Devianty (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
In terms of racial, ethnic and cultural diversity, Indonesia is a treasure. Language is another manifestation of this diversity. There are unique languages in almost every region in Indonesia. On the other hand, a group's culture will be easier to maintain if there is open dialogue between generations. When people from different cultural backgrounds engage in communicative activities, this is called cross-cultural communication. Basically, each person has a unique cultural identity, which shapes their views and way of thinking about the world. The more different two people's cultures are, the more difficult it is for them to communicate with each other.